Estructura diamétrica y diversidad de especies en bosque de terraza baja del distrito del Yavarí, Loreto, Perú. 2024 - Zambrano Ortiz, Paul Janffler (2025)
A study was conducted on the diameter structure and species diversity in a low terrace forest, in cutting plot 04 (PC 04) of the General Forest Management Plan (PGMF) for the forest concession 16-LOR-MAR/CON-MAD-2019-013, located in the district of Yavarí, Loreto. In plot 1, 38 species from 19 families and 34 genera were identified, with 518 individuals. The highest density was concentrated in the diameter classes of 10 cm (122 trees, 23,5%) and 50 cm (279 trees, 53,9%). In plot 2, 31 species from 18 families and 29 genera were recorded, with 389 individuals, with the highest density in the 50 cm class (211 trees, 54,2%). The Shannon-Wiener index (H′) was 3,09 in plot 1, indicating moderate to high diversity, dominated by Otoba glycycarpa (13,5%) and Eschweilera albiflora (12,5%). In plot 2, H′ was 2,88, reflecting moderate diversity, dominated by Otoba glycycarpa (16,7%) and Eschweilera albiflora (14,7%). Simpson's index (D) in plot 1 (0,0654) showed low dominance and high diversity, with Otoba parvifolia (pi=0,135) and Macrolobium ocaciifolium (pi=0,125) as the main ones. In plot 2, D was 0,08223, also with low dominance, highlighting the same dominant species. The Margalef richness index (DMg) was 5,92 in plot 1 and 5,03 in plot 2, showing moderate richness in both plots. These results show significant changes in diameter structure and diversity, reflecting the influence of environmental conditions in these ecosystems.